Isolating the role of corticosterone in the hypothalamic-pituitary-gonadal genomic stress response - Austin, Suzanne H; Harris, Rayna; Booth, April M; Lang, Andrew S; Farrar, Victoria S; Krause, Jesse S; Hallman, Tyler A; Macmanes, Matthew; Calisi, Rebecca M (bioRxiv, 2020)
ABSTRACT The negative impacts of stress on reproduction have long been studied. A large focus of investigation has centered around the effects of the adrenal steroid hormone corticosterone (CORT) on a system of tissues vital for reproduction, the hypothalamus of the brain, the pituitary gland, and the gonads (the HPG axis). Investigations of the role of CORT on the HPG axis have predominated the stress and reproductive biology literature, potentially overshadowing other influential mediators. To gain a more complete understanding of how elevated CORT, characteristic of the stress response, affects the activity of the HPG axis, we experimentally examined its role at the level of the genome in both male and female rock doves (Columba livia). We exogenously administrated CORT to mimic circulating levels during the stress response, specifically 30 min of restraint stress, an experimental paradigm known to increase circulating corticosterone in vertebrates. We examined all changes in genomic transcription within the HPG axis as compared to both restraint-stressed birds and vehicle-injected controls, as well as between the sexes. We report causal and sex-specific effects of CORT on the HPG stress response at the level of the transcriptome. Restraint stress caused 1567 genes to uniquely differentially express while elevated circulating CORT was responsible for the differential expression of 304 genes. Only 108 genes in females and 8 in males differentially expressed in subjects who underwent restraint stress and those who were given exogenous CORT. In response to CORT elevation characteristic of the stress response, both sexes shared the differential expression of 5 genes, KCNJ5, CISH, PTGER3, CEBPD, and ZBTB16, all located in the pituitary. The known functions of these genes suggest potential influence of elevated CORT on immune function and prolactin synthesis. Gene expression unique to each sex indicated that elevated CORT affected more gene transcription in females than males (78 genes versus 3 genes, respectively). To our knowledge, this is the first study to isolate the role of CORT in HPG genomic transcription during a stress response. These results provide novel targets for new lines of further investigation and therapy development. We present an extensive and openly accessible view of the role corticosterone in the HPG genomic stress response, offering novel gene targets to inspire new lines of investigation of stress-induced reproductive dysfunction. Because the HPG system is well-conserved across vertebrates, these data have the potential to inspire new therapeutic strategies for reproductive dysregulation in multiple vertebrate systems, including our own. Competing Interest Statement The authors have declared no competing interest. Footnotes * https://github.com/suzaustin/CORT.RS_DGE